Meat quality and health implications of organic and conventional beef production. (February 2015) - Kamihiro, S.; Stergiadis, S.; Leifert, C.; Eyre, M.D.; Butler, G.
Abstract: Recommendation to reduce fat consumption from ruminant meat does not consider the contribution of nutritionally beneficial fatty acids in lean beef. Here we report effects of production system (organic vs conventional) and finishing season on meat and fat quality of sirloin steaks from retail outlets and simulated fatty acid intakes by consumers. There was little difference in meat quality (pH, shear force and colour), but the fat profiles varied considerably between production systems and season. Meat fat from organic and summer finished cattle contained higher concentrations of conjugated linoleic acid, its precursor vaccenic acid and individual omega-3 fatty acids and had a lower ratio of omega-6 to omega-3 fatty acids compared with non-organic and winter finished cattle respectively. The fat profile from summer finished organic beef aligns better to recommended dietary guideline including those for long chain omega-3 fatty acids compared with that from winter finished, non-organic steak. Highlights: This paper considers meat and fat quality in retail sirloin steak. It considers the impact of organic vs. conventional and summer vs. winter purchase. Fatty acid profiles were influenced by both production system and season. Summer and organic finishing resulted in higher levels of beneficial fatty acids. Avoiding subcutaneous fat consumption will drastically reduce CLA intake.